Anion–π interaction–induced phase separation as a prebiotic pathway to oxygenation - Xiaokang Ren; Xiaowei Song; Lecheng Lyu; Michael W. Chen; Richard N. Zare; Yifan Dai (Proceedings of the National Academy of Sciences, 2025)
Compartmentalization and chemical reactivity serve as the key elements driving prebiotic chemistry for evolution and selection. However, the potential coupling of compartmentalization chemistry with the intrinsic chemical activity of prebiotic compartments remains largely unexplored. Here, we demonstrate that anion–π interactions, which are largely overlooked in the chemistry of phase transition, can drive the formation of micron-sized assemblies. These structures further recruit cations to form anion–π–cation triads. Such assemblies mediate spontaneous oxygenation reactions through their electrochemical environments. This process provides a plausible prebiotic pathway for bioenergetics and molecular oxygen generation on early Earth, leading to the formation of primitive pigments via the oxidation of small molecules and the nontemplated selection of protocells through oxidation-dependent lipid degradation. Our findings highlight a simple yet functionally significant noncovalent interaction that introduces chemical functions into self-assembly and phase transition chemistry, delivering generalizable principles for engineering electrochemically active supramolecular assemblies and a conceptual framework in understanding abiotic evolution and selection.